Analisis Pengaruh Utang Luar Negeri Dan Ekspor Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2015-2019: Analysis of the Influence of Foreign Debt and Exports on Economic Growth in Indonesia in 2015-2019 - Sri Rahayu Husen; Yofandi Djibran Himran; Amir Buhang (Jurnal Ilmiah Produktif, 2021)
This study aims to analyze the influence of Indonesia's external debt using multiple non-linear regression and obtained the reverse equation Y = 190,032 – 5,444 X1 + 2,233 X2. (a) constant 190.032, meaning that if the variable Foreign Debt (X1) and Exports (X2) is worth 0, then economic growth (Y) is 190,032. The correlation coefficient between variable foreign debt (X1) and Exports (X2) and Economic growth (Y), which is 0.949, means that the relationship between foreign debt and exports with economic growth (Y) in the category is powerful. The R2 value obtained is 0.900, which can be interpreted that the Foreign Exchange (X1) and Export (X2) variables contribute 90% to the Economic growth variable (Y). It is known that t calculates -2,218 < t table 2,920, so it is concluded that the variable of foreign debt (X1) has an insignificant partial effect on the Variable economic growth (Y), then Ha is rejected, and Ho accepted. The influence of the Export variable (X2) on Economic Growth (Y). It is known that t calculates 2,783 > of t table 2,920 Export variables (X2) have a partial effect on the Economic Growth (Y) variable. Ha is rejected, and Ho is accepted.